Actors of Contemporary World Politics: Trends of Development - M. M. Lebedeva (Vestnik MGIMO-Universiteta)
The article is devoted to tendencies of development of transnational actors in XXI century. It is shown that their activity intensified, became involved a large number of people and cover all areas. Non-state actors began to form various types of partnerships: with states and with each other. Also the resource base of transnational actors was expanded. They actively use information and analytical resources. In the analysis of contemporary issues of world politics the attitudes, interests etc. of various transnational actors must be taken into account.